How does bilingual experience influence novel word learning? Evidence from comparing L1-L3 and L2-L3 cognate status - Xue, Heng; Deng, Renhua; Chen, Yanyan; Zheng, Wenxin (Frontiers in Psychology, 2022)
Bilingual experience exerts a complex influence on novel word learning, including the direct effects of transferable prior knowledge and learning skill. However, the facilitation and interference mechanism of such influence has largely been tangled by the similarity of the previously learned word knowledge. The present study compared Chinese-English bilinguals’ paired-associate learning of nonwords in logographic and alphabetic writing systems. The logographic nonwords resemble the form and meaning of L1 Chinese words in varying degrees, being cognates, false cognates, or non-cognates of Chinese. The alphabetic nonwords resemble the form and meaning of L2 English words, being cognates, false cognates, or non-cognates of English. The learning sequence of logographic and alphabetic words was cross-balanced. The learning results were measured in production and recognition tasks. As for learning the logographic nonwords, both the recognition and production results showed that cognates were learned significantly faster than the non-cognates, and the false cognates were also learned significantly faster than the non-cognates. This suggests stronger facilitation rather than interference from L1 on novel word learning. As for learning the alphabetic nonwords, both the recognition and production results revealed that cognates were learned significantly faster than the non-cognates, but false cognates showed no advantage over the non-cognates. This indicates that interference from L2 is stronger than that from L1. Taken together, the results provide new evidence for the dissociable facilitation and interference effects of bilingual experience. These results carry potential educational implications in that learning novel words depends on substantial bilingual experience.